2019
DOI: 10.1037/dev0000707
|View full text |Cite
|
Sign up to set email alerts
|

Emerging behavior problems: Bidirectional relations between maternal and paternal parenting styles with infant temperament.

Abstract: The present study examined bidirectional effects between maternal and paternal parenting styles (authoritative, authoritarian, permissive) and infant temperament (negative affect, orienting/regulatory capacity, surgency) in a diverse sample of 201 mothers and 151 fathers. Using 3 waves of longitudinal data (prenatal, 6 months, and 18 months), this study examined (a) whether maternal and paternal parenting styles prospectively predicted infant temperament; (b) whether mother-and father-reported infant temperame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 67 publications
7
33
1
Order By: Relevance
“…These findings corroborate the bioecological model illustrating that development is embedded within different social interactions (Bronfenbrenner, 2004), such as in terms of child-father and child-mother dyads. These findings also support the fathering literature which emphasizes the critical role of paternal parenting in different aspects of development, such as psychosocial functioning (Möller et al, 2016) and behavioral outcomes (Wittig & Rodriguez, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…These findings corroborate the bioecological model illustrating that development is embedded within different social interactions (Bronfenbrenner, 2004), such as in terms of child-father and child-mother dyads. These findings also support the fathering literature which emphasizes the critical role of paternal parenting in different aspects of development, such as psychosocial functioning (Möller et al, 2016) and behavioral outcomes (Wittig & Rodriguez, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…For example, parents who are predisposed toward abusive behavior may lack appropriate coping and parenting skills that are required to manage young children with difficult temperaments (Maltby et al, 2018). Furthermore, difficult temperament in early childhood and negative parenting have been found to mutually exacerbate one another over time in bidirectional ways (Micalizzi et al, 2017; Wittig & Rodriguez, 2019). Therefore, it is possible that our results actually reflect transactions among adversity, temperament, and child behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…Planalp et al also found that infant surgency affected maternal playing behavior in addition to maternal caregiving, and approaching toys and a lot of laughter were also aspects of surgency. Although studies have shown that negative emotionality and orienting affected the way parents interact with their children or parenting style ( Scaramella et al, 2008 ; Wittig and Rodriguez, 2019 ), it is possible that parenting behaviors closer to the temperament may be more susceptible to children’s temperament. In the Japanese version of the IBQ used in this study, the dimensions related to crying, such as distress to limitation and fear, were classified as surgency, and thus may have been most strongly associated with maternal beliefs about infant crying.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent longitudinal research study, mothers’ higher authoritative parenting style predicted later infants’ greater orienting, while higher maternal permissive parenting style predicted later infants’ lower orienting. Conversely, infant orienting was shown to positively predict the mother’s subsequent permissive parenting style ( Wittig and Rodriguez, 2019 ). Bridgett et al (2009) also showed that initial lower levels of infant orienting predicted more negative parenting 14 months later.…”
Section: Introductionmentioning
confidence: 99%